Clean Water Quality Test in Hatalai Village, South Leitimur District - Nendissa, Andriana R.; Radjabycolle, Juliana C.; Ivakdalam, Lydia Maria (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Water quality is the main factor in developing a clean and healthy lifestyle (PHBS). Researchers in this study wanted to see the quality of water sources used by the people of Hatalai State. Hatalai Country is a country that is 5.9 km from Ambon City Center, with a population of 989 people, with steep conditions. However, it has quite a number of springs. There are many springs where water is used by the people of the country. For this reason, researchers feel it is necessary to conduct research on the physical quality of five water sources, with the aim of this research being to identify the physical conditions of water storage and distribution facilities, analyze the physical quality of water and provide recommendations for providing clean and healthy water. Research methods. This research uses a descriptive approach and laboratory analysis. Researchers made observations on the condition of the distribution, storage and utilization of water at the research location. Samples were taken in holding tanks from 5 springs which will then be analyzed in the laboratory. The research results show that according to quality standards, water that is good for PHBS and drinking has no taste. Testing for turbidity parameters in Alam, Wermaang, Tree Damar, and Waisaru water has met the water quality standard requirements because it does not exceed the maximum level of <3 NTU. The turbidity test results for water in Hatalai ranged between 0.27 - 0.33 NTU, meaning that water that is not turbid contains very little dangerous substances such as iron and manganese. In conclusion, the water quality in Hatalai State physically meets the health requirements for consumption. The reservoirs are all in good condition.